The Methodology of Mas’ud Samarkandi in Solving Jurisprudential Issues - Mamatovna, Usmonova Khulkar (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article discusses the scientific and theoretical sources and methods used by Mas’ud ibn Mahmud ibn Yusuf Samarkandi, who lived at the end of the 13th century and the beginning of the 14th century, in writing his work "Saloti Mas’udi". The article provides a detailed analysis, supported with examples, of his approach to resolving jurisprudential issues.